Pengaruh Disiplin Kerja terhadap Kinerja Guru dan Karyawan di SMA Negeri 1 Guntur - Mursidah Mursidah; Henry Yuliamir (Mahesa Research Center, 2026)
This article aims to analyze the influence of work discipline on the performance of teachers and staff at SMA Negeri 1 Guntur. The study focuses on how the level of employee discipline contributes to performance achievement within the school environment. To approach this issue, theories from human resource management related to work discipline and employee performance were employed. Data were collected through questionnaires distributed to teachers and staff as respondents, and were then analyzed quantitatively using validity testing, reliability testing, descriptive analysis, and simple linear regression to determine the effect of the independent variable on the dependent variable. The research findings indicate that the work discipline of teachers and staff falls into the high category, while their performance is categorized as good. Regression analysis demonstrates that work discipline has a positive and significant effect on the performance of teachers and staff. This study concludes that improving work discipline reflected through punctuality, compliance with regulations, and responsibility in completing tasks contributes significantly to enhancing the effectiveness and quality of employee performance at SMA Negeri 1 Guntur. Therefore, the discipline culture must continue to be strengthened as a strategy to improve performance.